2016
DOI: 10.1080/13621718.2015.1104206
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modelling of gas metal arc joining of aluminium alloy and galvanised steels in lap joint configuration

Abstract: Advanced pulsed current gas metal arc based processes are increasingly attempted for the joining of aluminium alloys and galvanised steel sheets. The bead profile and the thickness of the interfacial Fe-Al intermetallic (IMC) layer significantly influence the failure strength of these joints. Although several experimental studies have examined the nature and extent of the IMC phases and consequent joint strength, quantitative efforts to estimate bead profile and the IMC layer thickness as function of process c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…heat input from 36 to 53 J mm -1 increases corresponding joint strength from 188 to 206 MPa, and further rise in heat input decreases joint strength to 180 MPa 7) . The authors found phase layer thickness around 1.3 ~ 2 μm with maximum joint strength of 73 MPa for aluminium to GA sheets 45,46) , while joining with GI sheet exhibited higher joint strength of 210 MPa with phase layer thickness of 0.8 ~ 4.5 μm 7) . Milani et al 47) examined the influence of different filler wires -AA4043, AA4047 and Al-Si3-Mn -on joining of 2 mm thick AA5754 alloy and 3 mm thick GI steel sheets by CMT process.…”
Section: Gas Metal Arc Based Joiningmentioning
confidence: 97%
See 2 more Smart Citations
“…heat input from 36 to 53 J mm -1 increases corresponding joint strength from 188 to 206 MPa, and further rise in heat input decreases joint strength to 180 MPa 7) . The authors found phase layer thickness around 1.3 ~ 2 μm with maximum joint strength of 73 MPa for aluminium to GA sheets 45,46) , while joining with GI sheet exhibited higher joint strength of 210 MPa with phase layer thickness of 0.8 ~ 4.5 μm 7) . Milani et al 47) examined the influence of different filler wires -AA4043, AA4047 and Al-Si3-Mn -on joining of 2 mm thick AA5754 alloy and 3 mm thick GI steel sheets by CMT process.…”
Section: Gas Metal Arc Based Joiningmentioning
confidence: 97%
“…The authors found phase layer thickness around 5 ㎛ with Al-Si filler wire while the Al-Mg filler wire resulted in higher the phase layer thickness of 12 ~ 13 ㎛ 44) . Das et al 7,45,46) used a wide range of heat input from 36 ~ 126 J mm -1 for joining of aluminium alloy to GI and GA steel sheets by coldArc, a low heat input pulsed current GMA process. Fig.…”
Section: Gas Metal Arc Based Joiningmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported literatures suggest that the joint quality can be improved significantly by controlling the heat input [3][4][5] . Various methods such as laser beam and laser-arc hybrid joining 2,[6][7][8][9][10][11][12][13][14] , arc based joining [3][4][5][15][16][17][18][19][20][21][22][23] and friction stir welding [24][25][26] are employed to join aluminium and steel sheets with an aim to control the heat input during joining of such dissimilar material combinations.…”
Section: Introductionmentioning
confidence: 99%
“…Das et al 15 proposed a theoretical-experimental method to estimate the thickness of the Al-Fe IMC layer in a lap congu-ration. Song et al 16 studied the microstructures of butt joints made by the TIG welding-brazing method and composition of the Al-Fe IMC layer.…”
Section: Introductionmentioning
confidence: 99%